Conglutination and managerial dominance versus diversification of life values - Nato, Takatsugu [Verfasser] (My University, 1989)
"The view that Japanese management is not such a harmonised solidarity as would initially appear is discussed. Three groups within Japanese management are identified: the power elite, belongers and survivor. The percentage each group represents and group characteristics are given. The role of the power elite is discussed in greater detail with particular reference to the taxation system and the structure of wealth which operates within Japan." (author's abstract) ((en)) Der Beitrag will das Bild von der harmonischen Solidarität in japanischen Unternehmen korrigieren. Es werden drei Gruppen im Management nach ihrem Anteil an der Unternehmensmacht unterschieden. Dise Gruppen werden in Bezug zum japanischen Steuersystem und der Struktur des Wohlstands gesetzt. (IAB)
Vereinigung und Managerdominanz versus Diversifikation von Lebenswerten
Keywords: S 5 Organisationsentwicklung; G 2.3.5 Wirtschaftsstrukturwandel; G 2.1 Globalisierung; S 3.2 Unternehmen und Behörden; G 2.4.3 Privater & Familiärer Wandel; Management; Struktur; Steuern; Unternehmensführung; Wohlstand; Selbstverwirklichung; Berufsproblem